FAMILY EPHYDRIDAE - Mathis, Wayne Neilsen; Júnior, Francisco De Assis Rodrigues; Couri, Márcia Souto (Zootaxa, 2016)
This catalog presents 53 species of Ephydridae from Colombia that are classified into five subfamilies, 15 tribes and 26 genera. For each species we present the available geographical information.